MARRIAGE AS A RESPONSE TO PREMARITAL PREGNANCY: SOCIO-CULTURAL CONFINEMENT, LEGAL PLURALISM, AND RELIGIOUS PRAGMATISM IN NORTH HALMAHERA - Bakence, Lutfi; Sultan, Lomba; DL, Rahmatiah; Ridwan, Saleh (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Marriage involving pregnant women outside wedlock remains a critical socio-cultural and legal phenomenon in Indonesia, particularly in North Halmahera where family honor, religious authority, and customary law strongly influence communal life. This study aimed to explore how such marriages are understood, legitimized, and practiced by families, community leaders, and legal institutions. Using a qualitative case study approach, data were collected through in-depth interviews with religious leaders, adat leaders, government officials, parents, and young women, complemented by participant observation and document analysis, and analyzed with an interactive model of reduction, display, and conclusion drawing. The findings reveal that marriage is primarily arranged to safeguard family honor, with communities regarding it as the only socially acceptable corrective measure, while religious leaders across traditions adopt pragmatic interpretations, invoking public interest or redemption to justify the practice, and customary rituals together with state dispensations further reinforce its legitimacy. Although marriage resolves immediate stigma and reintegrates families socially, it simultaneously generates long-term vulnerabilities, including interrupted education, economic dependence, marital instability, psychological stress, and increased maternal and neonatal health risks. This study contributes to the sociology of law and religion by demonstrating how socio-cultural confinement, Islamic legal pluralism, and adat practices converge in eastern Indonesia, while underscoring the urgent need for holistic interventions that integrate sexuality education, family communication, religious engagement, and legal reform to protect women and children more effectively.